Diakonos and prostatis : Women"s patronage in Early Christianity - Osiek, Carolyn (HTS teologiese studies, 2005)
In spite of numerous studies on the patronage system in Mediterranean antiquity, little attention has been paid to either how the patronage of women was part of the system or how it differed. In fact, there is substantial evidence for women’s exercise of both public and private patronage to women and men in the Greco-Roman world, by both elites and sub-elites. This information must then be applied to early Christian texts to infer how women’s patronage functioned in early house churches and Christian life.